All Questions Topic List
Integration Questions
Previous in All Question Next in All Question
Previous in Integration Next in Integration
Question Number 68434 by mhmd last updated on 10/Sep/19
Answered by mind is power last updated on 10/Sep/19
∫abf(x)dx=∫abf(a+b−x)dxletf(x)=3sin(x)−2sin2(x)sin(x)+cos(x)∫π6π3f(x)dx=∫π6π3f(π2−x)dx=∫π6π33cos(x)−2cos3(x)sin(x)+cos(x)dx2∫π6π3f(x)dx=∫π6π33sin(x)−2sin2(x)cos(x)+sin(x)dx+∫π6π33cos(x)−2cos3(x)cos(x)+sin(x)dx=∫π6π33sin(x)+cos(x)−2sin3(x)−2cos3(x)sin(x)+cos(x)dx=∫π6π33(sin(x)+cos(x))−2(sin(x)+cos(x))(sin2(x)+cos2(x)−cos(x)sin(x))sin(x)+cos(x)dx=∫π6π33−2(1+sin(x)cos(x))dx=∫π6π31−2sin(x)cos(x)dx=[x+cos2(x)]π6π3=π6+14−34=π−36
Terms of Service
Privacy Policy
Contact: info@tinkutara.com